BLUE MOON : A JACK REACHER NOVEL - Child, Lee (New York : Delacorte Press, 2019)
"When Myriam, a French-Moroccan lawyer, decides to return to work after having children, she and her husband look for the perfect nanny for their two young children. They never dreamed they would find Louise: a quiet, polite, devoted woman who sings to the children, cleans the family's chic apartment in Paris's upscale tenth arrondissement, stays late without complaint, and hosts enviable kiddie parties. But as the couple and the nanny become more dependent on one another, jealousy, resentment, and suspicions mount, shattering the idyllic tableau"
Translated from the French.
Keywords: Reacher, Jack -- (Fictitious character) -- Fiction; Retired military personnel -- Fiction; Older people -- Crimes against -- Fiction; Secrecy -- Fiction; Gangs -- Fiction; Thrillers (Fiction).